Evaluation of the efficacy of triazavirin versus oseltamivir in management of COVID-19 - Sara Samir Mohamed Elmenshawy; Mohamed Farouk Ahmed Abdelsalam; Tarek Refaat El Nagdy; Mohamed Abdel Salam Elgohary; Nagwa Ali Sabri; Amal El-kholy (Future Science OA)
Aim: To compare the safety and efficacy of triazavirin (TZV) 250 mg capsules versus oseltamivir 75 mg capsules in the treatment of individuals diagnosed with COVID-19.Materials & methods: A double-blind, randomized, interventional pilot study was conducted in a parallel design with a 7-day treatment period.Results: The results showed that TZV is superior to oseltamivir regarding length of hospital stay, days until clinical symptoms improvement, and cure of chest pneumonia.Discussion: Different literature data indicate the superiority of TZV in treating COVID-19 when compared with other therapeutic agents. While there is controversy about the efficacy of oseltamivir.Conclusion: It was concluded that TZV is more effective than oseltamivir in the management of COVID-19 disease.Trial registration number: NCT04973462.